The Influence of Different Phases of a Solar Flare on Changes in the Total Electron Content in the Earth’s Ionosphere - Susanna Bekker; Ryan O. Milligan; Ilya A. Ryakhovsky (The Astrophysical Journal, 2024)
Variations in X-ray and extreme ultraviolet (EUV) irradiance during solar flares lead to a noticeable increase in the electron concentration in the illuminated part of the Earth’s ionosphere. Due to the large amount of experimental data accumulated by global navigation satellite systems, the total electron content (TEC) response to the impulsive phase of a solar flare has been studied quite well. However, recent studies have shown that a large fraction of X-class flares have a second strong peak of warm coronal emission (which is called “EUV late phase”), whose influence on the ionization of ionospheric layers is not yet clear. A combined analysis of successive solar emissions and the caused TEC changes made it possible to numerically estimate the ionospheric response to the impulsive, gradual, and late phases of the X 2.9 solar flare that occurred on 2011 November 3 and demonstrate the high geoeffectiveness of the rather weak Fe xv 28.4 nm solar emission during the EUV late phase. It was found that the ionospheric response to the relatively weak emissions of the EUV late phase of the X 2.9 solar flare amounted to almost a third of the TEC increase during the impulsive phase.